2009
DOI: 10.1016/j.ultrasmedbio.2009.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Dual Frequency Method for Simultaneous Translation and Real-Time Imaging of Ultrasound Contrast Agents Within Large Blood Vessels

Abstract: A dual frequency excitation method for simultaneous translation and selective real-time imaging of microbubbles is presented. The method can distinguish signals originating from free flowing and static microbubbles. This method is implemented on a programmable scanner with a broadband linear array. The programmable interface allows for dynamic variations in the acoustic parameters and aperture attributes, enabling application of this method to large blood vessels located at varying depths. The performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 32 publications
0
65
1
Order By: Relevance
“…Applying radiation force orthogonal to the flow in large arteries to stop flowing MB remains a challenge as mean velocities can reach several cm/s. Patil et al 17 reported that, even when excited near resonance, a mechanical index of 0.15 was required to halt MB for a wall shear rate of 52 s −1 . Moreover, flowing MB clusters can impede accumulation by engulfing already bound targeted MB.…”
mentioning
confidence: 99%
“…Applying radiation force orthogonal to the flow in large arteries to stop flowing MB remains a challenge as mean velocities can reach several cm/s. Patil et al 17 reported that, even when excited near resonance, a mechanical index of 0.15 was required to halt MB for a wall shear rate of 52 s −1 . Moreover, flowing MB clusters can impede accumulation by engulfing already bound targeted MB.…”
mentioning
confidence: 99%
“…Low-pass filtering in slow-time dimension is designed to suppress highfrequency circulating microbubble signals while retaining low-frequency adherent microbubble signals [45]- [48]. Similarly, slow-time averaging is designed to cancel out more random signals derived from circulating microbubbles while retaining stationary signals from adherent microbubbles [49], [50]. "Dwell time" is another threshold-determined parameter used to quantify the inter-frame signature of microbubbles.…”
Section: Differentiation Of Adherent From Freely Circulating Microbubmentioning
confidence: 99%
“…tumor) has been demonstrated, studies were performed in large blood vessel environments with application of ARF in vitro and ex vivo [23], [45], [49], [50], [64]. Due to the high flow rate and shear forces, ARF is essential in large vessels to push microbubbles towards the distal vessel wall.…”
Section: Assistance Of Acoustic Radiation Force (Arf)mentioning
confidence: 99%
See 2 more Smart Citations